2016
DOI: 10.1039/c5ra19947f
|View full text |Cite
|
Sign up to set email alerts
|

Substrate stiffness does affect the fate of human keratinocytes

Abstract: Epithelial cells response to the varying stiffness of polydimethyl siloxane (PDMS) substrate.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
17
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 28 publications
(19 citation statements)
references
References 46 publications
2
17
0
Order By: Relevance
“…On the other hand, when cultured on a slightly stiffer matrix (10 kPa and 20 kPa) cells showed survival and showed higher proliferation as compared to TCP (Fig. 1) which has also been shown with PDMS 30. This concludes that stiffness not only plays a critical role in regulating the proliferation but is also involved in cell survival.…”
Section: Discussionsupporting
confidence: 59%
“…On the other hand, when cultured on a slightly stiffer matrix (10 kPa and 20 kPa) cells showed survival and showed higher proliferation as compared to TCP (Fig. 1) which has also been shown with PDMS 30. This concludes that stiffness not only plays a critical role in regulating the proliferation but is also involved in cell survival.…”
Section: Discussionsupporting
confidence: 59%
“…Analysis at the nuclear level, showed that the soft surface caused nuclear mechanotransduction (evident from nuclear lamin A/C expression) and perturbed the transcription pattern of protein (VEGF as model protein) in HaCaT cells. This study confirmed that the human keratinocytes are mechanosensitive toward substrate 55 .…”
Section: Biological Performance Of Electrospun Matssupporting
confidence: 83%
“…On the other hand, the cells grown on the 1 µm CL materials were about as active as those grown on the 1 µm µCP materials. In a recent study by Gupta et al [58], it was reported that keratinocyte proliferation increased with an increased PDMS surface stiffness (0.05–1.6 MPa) [58]. This could be an explanation as to why some CL surfaces, which were stiffer, had >150% of dye reduction, while the dye reduction of all the softer µCP surfaces was <150%.…”
Section: Discussionmentioning
confidence: 99%